Comparison Of Genotypes And Virulence Factors Among Carrier And Pathogenic Strains Of Candida Albicans - Zain Illyaaseen, Khairudin (2021)
Candida albicans is a prominent global fungal pathogen capable of causing fatal systemic infections in humans. Presently in Malaysia, there is little data on genetic diversity of this organism and behavioural characteristics of local organisms. In this project, three genotyping methods; 25S rDNA genotyping, ALT sequence typing and MLST were applied to study genetic diversity whereas antifungal susceptibility test, gene expression assay and biofilm formation assay were used to assess some behavioural criteria. This study found that the most common genotype was A, accounting for approximately 70% of the 111 isolates tested. MLST analysis showed a statistically significant association between pathogenicity and a group of closely related isolates. All isolates tested were shown to be susceptible to both nystatin and fluconazole. No statistically significant difference was found between the biofilm forming ability of isolates of pathogenic or commensal origins. qPCR assays revealed the upregulation of HWP1 as a virulence gene in the representative isolates from pathogenic origin. While the distribution of 25S rDNA genotypes mostly matched previous studies done elsewhere, MLST data showed that there may yet be iii many novel sequence types in Malaysia which have yet to be catalogued. In the future, greater efforts in genotyping for proper documentation of genetic diversity would be beneficial with focus on greater research into the genomes of isolates exhibiting enhanced virulence.